Challenges and Coping Mechanisms: Women Entrepreneurs in Indonesia Amidst COVID-19 - Ahmi Husein, Muhammad; Nur Arumsari, Devinta (Universitas muhammadiyah malang, 2025)
This study explores how women entrepreneurs in Indonesia coped with the challenges of the COVID-19 pandemic using a qualitative thematic analysis. Interviews were conducted with 5 women entrepreneurs across various sectors and regions, including rural and urban areas. The analysis revealed three key coping strategies: reliance on informal financial networks, digital adaptation, and emotional resilience. Women in rural areas leaned heavily on informal financial mechanisms like community savings groups to sustain their businesses, while urban entrepreneurs successfully adopted digital platforms to reach new markets despite the physical restrictions. Emotional resilience, often supported by family networks, was crucial in helping entrepreneurs balance business challenges and increased domestic responsibilities during the pandemic. The study highlights the gendered nature of these coping mechanisms and the structural barriers faced by women entrepreneurs, such as limited access to formal financial institutions and the digital divide between rural and urban areas. Recommendations include expanding access to formal financial services, improving digital infrastructure, and providing support systems that recognize the dual roles women play as business owners and caregivers. This research emphasizes the need for more inclusive policies to support women entrepreneurs in crisis situations.